Parklets As Public Space - Elif KORKMAZ (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA, 2024)
The unpredictable increase in the number of motor vehicles and the population due to changes in the urban structure has revealed the need for new public areas, recreation and social contact points for pedestrians, especially in city centers. Parklet designs, can be installed modularly on the one or more car parking area, are carried out in order to calm traffic, to ensure pedestrian safety, and to create public spaces. For this purpose, within the scope of the study, public space and the process of change are revealed, and parklets designed with urban equipment elements (street furniture) to meet various public needs, especially in city centers, are examined through examples from our country (Istanbul Metropolitan Municipality example) and the world. As a result, parklet designs, which are designed in a modular structure and allow alternative designs in different regions, include innovative approaches to publicity for Istanbul and all our other cities.